Pemetaan Pemetaan sebaran Terumbu Karang di Perairan Pulau Kelapan, Kabupaten Bangka Selatan Berdasarkan Data Satelit Sentinel 2A - Khoirul Amrillah; Wahyu Adi; Kurniawan Kurniawan (Universitas Bangka Belitung, 2019)
The purpose of this study was to analyze a map of the distribution of coral reefs based on satellite image data of Sentinel 2A, analysis the extent of the coral reefs in shallow waters of Kelapan Island, and analysis of the condition coral reefs (percentage cover, mortality index, and genus diversity) based on the diving data analysis. This research carried out in Kelapan Island waters, South Bangka Regency. The research method used digital image processing, ground check based on digital image maps, coral reef data retrieval, and measurement of environmental parameters. The data analysis used coral reef calculates percentage of cover and mortality index. The results show the distribution of coral reefs in Kelapan Island, South Bangka Regency based on on satellite image data of Sentinel 2A it has 4 class which is coral reefs, algae, sand, and algae mix sand using supervised classification method and coordinate projection WGS 1984 which 16.5 Ha or 12.2% area. The condition of coral reefs at stations 1 and 2 in a very good category with cover of 75.54 and 78.88% covers, station 3 in the medium category with 49.94%, and at station 4 including a good category with 63.74%. The Mortality Index ranges from 0.012 - 0.486. The genus diversity found 19 genuses. Generally, the results of environmental measurements parameters in the waters support the survival of coral reef ecosystems.